2017
DOI: 10.3892/ijo.2017.4104
|View full text |Cite
|
Sign up to set email alerts
|

Nano Let-7b sensitization of eliminating esophageal cancer stem-like cells is dependent on blockade of Wnt activation of symmetric division

Abstract: The poor therapy response and poor prognosis of esophageal cancer has made it one of the most malignant carcinoma, and the complicated multidisciplinary treatment failed to achieve a long-term disease-free survival. To diagnose esophageal cancer at an earlier stage, and to improve the effect of anticancer therapy would improve the therapeutic efficacy. After retrospective analysis of the cancer samples of patients who received esophagectomy, we found the relevance between ratio of either ALDH1 or CD133-positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…Total RNA was extracted from surgical specimens and cultured cells using RNAiso Plus (Takara Biotechnology Co., Ltd.) according to the manufacture's protocol. Reverse transcription was performed using PrimeScript™ RT Reagent kit (Takara Biotechnology Co., Ltd.) as previously described (24). PCR was conducted using SYBR ® Premix Ex Taq™ II (Tli RNaseH Plus2X; Takara Biotechnology Co., Ltd.) on a CFX96TM Real-Time PCR Detection System (Bio-Rad Laboratories, Inc.).…”
Section: Reverse Transcription-quantitative Pcr (Rt-qpcr)mentioning
confidence: 99%
“…Total RNA was extracted from surgical specimens and cultured cells using RNAiso Plus (Takara Biotechnology Co., Ltd.) according to the manufacture's protocol. Reverse transcription was performed using PrimeScript™ RT Reagent kit (Takara Biotechnology Co., Ltd.) as previously described (24). PCR was conducted using SYBR ® Premix Ex Taq™ II (Tli RNaseH Plus2X; Takara Biotechnology Co., Ltd.) on a CFX96TM Real-Time PCR Detection System (Bio-Rad Laboratories, Inc.).…”
Section: Reverse Transcription-quantitative Pcr (Rt-qpcr)mentioning
confidence: 99%
“…Total RNA was isolated using TRIzol ® (Invitrogen; Thermo Fisher Scientific, Inc.) according to the manufacturer's protocol. cDNA was synthesized from RNA using a PrimeScript™ RT Reagent kit (Takara Biotechnology Co., Ltd., Dalian, China) as previously described (25). RT-qPCR was performed using SYBR ® Premix Ex Taq™ II (Tli RNaseH Plus 2X; Takara Biotechnology Co., Ltd.) on a CFX96™ Real-Time PCR Detection system (Bio-Rad Laboratories, Inc., Hercules, CA, USA).…”
Section: Reverse Transcription-quantitative Polymerase Chain Reactionmentioning
confidence: 99%
“…Snai1 is a critical transcription factor for EMT by binding to and sequentially inhibiting E‐cadherin promoter, which reduced cell adhesion and promoted migratory capacity. In addition, current studies have shown that Snai1 is implicated in the regulation of chemo‐resistance and the emergence of cancer stem‐like cell (CSC) phenotype . The further elucidation of Snai1 in EMT and CSC provides a critical insight into the development of metastatic cancer and long‐term recurrence.…”
Section: Introductionmentioning
confidence: 99%